The Relationship Between Family Knowledge, Family Education, and Anxiety Levels Among Family Members of ICU Patients - Okta Vergia; Nurwijaya Fitri (Inspirasi Foundation, 2026)
Introduction: Family members of critically ill patients in the Intensive Care Unit (ICU) often experience significant anxiety due to uncertainty about the patient’s condition, highlighting the importance of family knowledge and education in reducing psychological distress. Objective: This study aims to analyze the relationship between family knowledge and education level and the anxiety levels of family members of patients treated in the Intensive Care Unit (ICU) at Bakti Timah Pangkalpinang Hospital in 2025. Method: This quantitative research with a cross-sectional design aims to analyze the relationship between family knowledge and education towards the anxiety level of family members of patients who were treated in the ICU of Bakti Timah Pangkalpinang Hospital in 2025. By using a sample of 61 respondents selected through the Simple Random Sampling technique. Result: The results of the Chi-Square test showed a significant relationship between family knowledge and anxiety levels (p-value = 0.000; POR = 10.00), where less knowledge is 10 times more at risk of experiencing anxiety. Similarly, a significant relationship was found between family education and anxiety levels (p-value = 0.000; POR = 5.00), indicating that low education increased the risk of anxiety 5 times greater. Conclusion: The conclusion shows that family knowledge and education are important factors that affect anxiety. Therefore, it is recommended to improve therapeutic communication training for nurses and ensure optimal information provision and psychological support to reduce the patient’s family anxiety level.